Dilemma between universal science and national science. Linking academia- productive sector during the developmentalism (2015)
This paper aims to recover the debates, speeches and actions that the Faculty of Exact and Natural Sciences of the University of Buenos Aires (Argentina) crossed during the 60s and 70swhen the definition of a scientific policy, around the development of "national science", involved a positioning with regards to the binomial science-ideology.Through a documentary research, interviews, and mainly through a literature review, we attempted to reconstruct the scene of dispute over debates, which are contextualized in history but are awaiting and stress the definitions of scientific policy.From the lack of entailment between knowledge production and development in the FCEN imprint, criticism about the flow of scientific and technological knowledge transferred from the outside, the informality in linking particular actions, and the signing of the first contracts by the FCEN, we tried to highlight with original contributions and unpublished documents a valid and critic revelation regarding the nostalgic look  at the "golden age" of the Faculty of Exact and Natural Sciences of the University of Buenos Aires.